Characterizing landscape fragmentation of Koitobos river sub-basin, Trans-Nzoia, Kenya - Kennedy Wekesa Murunga; Maurice Nyadawa; Joseph Sang; Charles Cheruiyot (Heliyon, 2024)
The changes in landscape structure and functioning due to unprecedented human interference are hastening across the globe and it is thus a compelling necessity to preserve and restore our ecosystems. This study aimed to characterize levels of landscape fragmentation, habitat structure, driving forces, and perceptions of the residents on the most preferred reconfiguration approaches. The land use/land cover [LULC] change was first determined by interpreting the 1973, 1986, 1995, 2002, 2014, and 2022 Landsat images using the QGIS 3.26 while the selected landscape fragmentation metrics were analyzed using FRAGSTATS 4.2. Forests, shrubs, and grasslands showed a declining trend, except for agriculture, water, and built-up areas, which depicted high increases for the study periods [1973 to 2022]. The landscape of the study area is characterized as progressively fragmenting as signified by high escalated values of patch number [374 %], edge density [7828 %] between 1986 and 2002, contagion [10.3%], and a declined value of Shannon Diversity Index [SHDI] [-17.42%], Shannon evenness index [SHEI] [-25.8 %] and connectedness [-43.3%]. Considering these results, high losses of forests and grasslands coupled with expansive farmlands and built-up areas have led to unprecedented landscape fragmentation From field surveys and oral interviews, this has not only left streams vulnerable to massive sediment loads but has also triggered annual floods which occur during wet months even though change in onset of rainfall seasons was also reported. The findings call for restoration and integrated and sustainable restoration efforts, especially for the forests, grasslands, and riparian corridors along with sustainable urban planning and community-based sensitization on watershed management.